Refining a DEI Assessment Tool for Use in Optimizing Professional STEM Societies for Gender Equity - Leibnitz, Gretalyn M.; Peters, Jan W.; Campbell-Montalvo, Rebecca; Metcalf, Heather; Lucy Putwen, Andrea; Gillian-Daniel, Donald L.; Sims, Ershela L.; Segarra, Verónica A. (Frontiers in Sociology, 2022)
Historic science, technology, engineering and mathematics (STEM) disciplinary cultures were founded in a system that was predominately male, white, heterosexual, and able-bodied (i.e., “majority”). Some societal norms have changed, and so has demand for inclusive STEM engagement. However, legacy mental models, or deeply held beliefs and assumptions, linger and are embedded in the STEM system and disciplinary cultures. STEM reform is needed to maximize talent and create inclusive professions, but cannot be achieved without recognizing and addressing norms and practices that disproportionately serve majority versus minoritized groups. As leading voices in disciplinary work and application, disciplinary and professional societies (Societies) are instrumental in shaping and sustaining STEM norms. We, leaders of the Amplifying the Alliance to Catalyze Change for Equity in STEM Success (ACCESS+) project, recognize the need to provide Society diversity, equity, and inclusion (DEI) change leaders with tools necessary to foster systemic change. In this Perspectives article, we present the Equity Environmental Scanning Tool (EEST) as an aid to help Society DEI change leaders elucidate legacy mental models, discern areas of strength, identify foci for advancement, and benchmark organizational change efforts. We share our rationale and work done to identify, and, ultimately, adapt a Society DEI self-assessment tool from the United Kingdom. We share background information on the UK tool, content and structural changes made to create the EEST, and an overview of the resulting EEST. Ultimately, we seek to increase awareness of a Society-specific DEI self-assessment tool designed to help Society DEI change leaders advance inclusive reform.